The Effect of the Fan ‘n Pick Learning Method on Students’ English Speaking Ability - Aulia, Dewi Monika; Pratama , Hendi (LITPAM, 2026)
English speaking ability is an essential productive skill in foreign language learning, particularly for vocational high school students who are expected to communicate actively and practically. However, speaking instruction in classrooms often encounters obstacles, such as low student participation and the use of less interactive learning methods. This study aims to examine the effect of the Fan ‘n Pick learning method on the English speaking ability of Grade XI students at SMK Negeri 1 Pringapus. This study employed a quasi-experimental method with a pretest–posttest control group design. The research sample consisted of 70 students divided into an experimental group and a control group, each comprising 35 students. The experimental group was taught using the Fan ‘n Pick method, while the control group received conventional instruction. The research instrument was a speaking ability test covering aspects of pronunciation, grammar, vocabulary, fluency, and comprehension. Data were analyzed using the Wilcoxon test and the Mann–Whitney test. The results showed a significant improvement in speaking ability in the experimental group, with the mean score increasing from 63.43 to 82.43 (p = 0.001). The control group did not show a significant improvement (p = 0.399). The difference in the mean Δ scores between the two groups was also statistically significant (p = 0.001). The conclusion of this study indicates that the Fan ‘n Pick learning method has a significant